A study on the role of bank in the growth of indian economy - ROBERT, MR.P. WILLIAM; K, MR. KRISHNABALA (The journal of contemporary issues in business and government, 2020)
Banking sector in India witnessed a tremendous growth because of innovation technology and product. The research paper titled the role of banks in the growth of Indian economy. This paper studies factors influencing the role of the Bank in the growth of Indian economy. Descriptive research is applied using a convenience method of sampling 109 respondents. The tools used for the study are mean analysis, frequency analysis, t-test, ANOVA and factor analysis. It is found that Modern business, business facilitator, employment opportunity, banking services, finance assistance, agricultural sector, trade, loans are the factors influencing the role of the Bank in growth of Indian economy and there is no significant difference between the customers and perception towards Indian economy.